La biodiversité, entre appropriation privée, revendications de souveraineté et coopération internationale - Daniel Compagnon (Développement Durable et Territoires)
Notions like “global commons” and “global public goods” do not easily apply to biodiversity because the latter is claimed by the states in the name of sovereignty and apportioned to business companies in the context of a globalised market. Moreover conservation and management policies do not look alike at local, national and international levels. Therefore this coordination between international regimes and national and local levels is the main challenge of a truly transcalar biodiversity governance